Pengembangan Aplikasi Pengingat Jatuh Tempo Pembayaran Tagihan Berbasis Android - Yansen; Ester Lumba (UNIVERSITAS KALBIS, 2022)
The purpose of this research is to develop bill payment reminder android bassed application. The software development method used in this research is the Rational Unified Process (RUP) with Unified Modeling Language (UML) modeling. It was built using an Android Studio device with the Java programming language, PHP, and MariaDB as a database. It offers an alternative to bill payment reminders using the push notification feature. The billing reminder can be done by entering the billing data based on the time of payment, then the application generates reminders in the form of notifications to help the bill owner in remembering the time of payment.